Conclusions from the HIV in Europe Copenhagen 2012 Conference and ways forward: working together for optimal HIV testing and earlier care. (28th August 2013) - Raben, D; Delpech, V; de Wit, J; Sullivan, A; Lazarus, JV; Dedes, N; Coenen, T; Lundgren, J; ,
Abstract : The objective of this article is to set the scene for this supplement by presenting and discussing the overall outcomes of the HIV in Europe Copenhagen 2012 Conference and how the HIV in Europe initiative intends to further address challenges and themes raised during the conference.